Princípio do crédito responsável: evitabilidade do superendividamento e promoção da pessoa humana na sociedade de consumo - Carqui, Vagner Bruno Caparelli (2016)
The consumer society has promoted significant changes in the recognition of the individual to society. The radicalization of consumerism that made possible by the credit democratization broadened access of these individuals to the market, with no adequate financial education. Consumer promotion polices, combined with the use of marketing mechanisms, promoted a society that is embodied by the consumption of goods and services, without proper regulation by the Government. In this context, the called Postmodernity is taken to represent this new phase of consumers behavior, in a context of promotion and exploitation of consumer credit. In evidence, the radicalization of consumption without proper regulation promoted the expansion of the risks related to the asymmetry between suppliers and consumers that exists in the market as the over-indebtedness as a risk arising from the radicalized consumer society that the limits the consumption capacity of over indebtedness of individuals of “good intentions”. Thus, this work approaches the over-indebtedness as a risk arising from the radicalized consumer society that limits the consumption capacity of over-indebted consumers and leads to the deprivation of the capacity to exercise rights. The lake of specific legislation for the over-indebtedness theme opens a gap in the protection of this hypervulnerable subject, imposing the need to consider the credit in your three-dimensional aspect: as consumer law, as duty of supplier, finally, as a legal principle to be able for printing new borders to consumer relations, promoting the protection of the dignity of the human person, as the ultimate purpose of the democratic rule of law. Using the deductive method, with special reference to legal arguments, this work has as main objective to present the need for a new three-dimensional design credit, necessary to protect consumers inserted in the radicalization stage of the consumer society.